Electric Energy Potential from Pineapples and Potatoes - Atikah Nur Syahirah; Riska Cahyati (Universitas Negeri Medan, 2021)
Basically, the voltage can be obtained from various sources, including fruit. Fruit is often used as food, drink and a source of vitamins for the body's defense system. It turns out that it has the ability to generate electricity, especially for fruit that has a high acidity level. The acidity in some types of fruit is able to generate electricity because it is electrolyte. Fruits which contain mineral acids in the form of hydrochloric acid and citric acid, are strong electrolytes that break down completely into ions in a water solution. Besides having acid, fruits also contain a lot of water, so that when two different metals are immersed, the fruit solution will create a potential difference between the metal and water so that there is an electrode potential that can generate electric current as well. The purpose of making a rough draft of this practicum is to prove the existence of electrical energy in pineapples and potatoes. In this experiment, it has been proven that pineapples and potatoes can produce an electric current, indicated by the presence of a voltage when measured by a voltmeter.